2020
DOI: 10.1186/s40561-020-00129-4
|View full text |Cite
|
Sign up to set email alerts
|

G4D - a treasure hunt game for novice programmers to learn debugging

Abstract: Visual Programming Environments (VPEs) are predominantly being used to teach programming concepts through interactive games with interesting narratives. Games have been developed to teach basic concepts of programming such as deriving logic, writing code, debugging the code and so on. Debugging code is one of the most important activities that can improve the skill of tackling a problem. In programming, one needs to identify the correct location of an error and fix it, which is usually learned through experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…For example, researchers have adopted the problem‐based learning strategy (Chang, Chung, & Chang, 2020), a structured‐resource issue‐quest approach (Hsu & Hwang, 2017), design thinking disposition (Tsai & Wang, 2020), or game‐based learning (Jantan & Aljunid, 2012) to support programming training, and have argued that integrating various teaching and learning strategies benefited learners' learning performance, and promoted their satisfaction, enjoyment and motivation in computer programming. Venigalla and Chimalakonda (2020) adopted learning strategies with debugging practice to train students' programming ability, and found that students' confidence in learning programming was promoted after they participated in the guided debugging practices in the programming course (Chiu & Huang, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, researchers have adopted the problem‐based learning strategy (Chang, Chung, & Chang, 2020), a structured‐resource issue‐quest approach (Hsu & Hwang, 2017), design thinking disposition (Tsai & Wang, 2020), or game‐based learning (Jantan & Aljunid, 2012) to support programming training, and have argued that integrating various teaching and learning strategies benefited learners' learning performance, and promoted their satisfaction, enjoyment and motivation in computer programming. Venigalla and Chimalakonda (2020) adopted learning strategies with debugging practice to train students' programming ability, and found that students' confidence in learning programming was promoted after they participated in the guided debugging practices in the programming course (Chiu & Huang, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that the game environment was most effective at teaching debugging for students with little previous experience, but some students found the environment frustrating. More recently, Venigalla and Chimalakonda [89] developed G4D, a debugging game in which students debug C code to control a character searching for treasure. Although students were positive about the tool, the impact on debugging was not measured.…”
Section: Teaching Students To Debugmentioning
confidence: 99%
“…Con el aumento de las tasas de aceptación de los entornos de enseñanza y aprendizaje en línea, se están desarrollando varias herramientas para enseñar a programar y hacer que el aprendizaje sea interactivo, creativo, e interesante, utilizando diversas tecnologías, como la realidad mixta, la inteligencia artificial, etc. (Venigalla y Chimalakonda, 2020). Sin embargo, para preparar a nuestros jóvenes para enfrentarse al mundo en el que les tocará vivir, necesitamos un cuarto bloque que podríamos etiquetar como lenguaje Revista e-Ciencias de la Información revista.ebci@ucr.ac.cr | http://revistaebci.ucr.ac.cr | ISSN 1659-4142 6 digital, que incorporaría las competencias necesarias para desenvolverse con éxito en el mundo digital, con la programación como forma de resolver problemas y el pensamiento computacional como paradigma de trabajo (Llorens, 2015).…”
Section: Programación Por Bloquesunclassified